Family Environment as a Determinant of Learning Motivation in Culinary Students at SMK N 9 Padang - Hayati, Yuri; Gusnita, Wiwik; Kasmita, Kasmita; Andriani, Cici (Universitas Negeri Padang, 2025)
This research is based on issues related to the low learning motivation of students, which needs to be addressed by understanding the factors influencing motivation, particularly the family environment. The objectives of this study are: 1) To describe the living conditions of eleventh-grade Culinary students at SMK Negeri 9 Padang, 2) To describe the learning motivation of eleventh-grade Culinary students at SMK Negeri 9 Padang, 3) To analyze the impact of the family environment on the learning motivation of eleventh-grade students at SMK Negeri 9 Padang. The research employs a quantitative method with a correlational. The population of this study consists of 224 students in the Culinary program at SMK Negeri 9 Padang. The sample includes 145 students, selected through random sampling techniques. Data were collected by distributing research questionnaires directly at the school, which were tested for validity and reliability. Data analysis was conducted using both descriptive and inferential analysis methods. The results of this study indicate that : 1) Family Enviroment of student in the XI Culinary class at SMK Negeri 9 Padang is categorized as high. 2) The learning motivation of students in the XI Culinary class at SMK Negeri 9 Padang is categorized as moderate 3) There is a positive and significant influence of the family environment on the learning motivation of students in the XI Culinary class at SMK Negeri 9 Padang. If the family environment of the students is low, then motivation to learn is low.